Konseling Keluarga dalam PersePeKtif HuKum islam - El-Fiah, Rifda (Universitas Islam Negeri Raden Intan Lampung, 2016)
Family counseling in the perspective of Islamic law, is a process of providing assistance to individuals/groups in afamily, provided by a counselor (someone who helps), to the the counselee (people assisted) to be aware of his/her existence as a creature of God, with his/her position as a family member. It is important in order to be in harmony with the provisions and wills God, to achieve the happiness in this world and in the hereafter. A family which is formed by someone, is essentially an attempt to obtain happiness and wellbeing. It formed to channel the sexual appetite (biological), to combine a sense of love and affection between two person, which continues to spread compassion and maternal and paternal affection to all members of the family (the descendants). Besides the fact that there always some problems in marriage and family life, it indicates that counseling which is based on the values of Islam (Islamic law) becomes a necessity. This paper attempts to give a new perspective of a counselor in helping Muslim families to overcome their problems, bsaed on the law or the rules of Islam.